2014
DOI: 10.1111/epi.12690
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive use of controlled‐release pregabalin in adults with treatment‐resistant partial seizures: A double‐blind, randomized, placebo‐controlled trial

Abstract: SUMMARYObjectives: To assess the efficacy and tolerability of add-on pregabalin controlledrelease formulation (PGB-CR) (doses of 165 or 330 mg/day) in patients with partialonset seizures (POS). Methods: This was a randomized, double-blind (DB), parallel-group study of PGB-CR once-daily as adjunctive treatment in adults with treatment-resistant partial seizures. After an 8-week baseline period, eligible patients were randomized (1:1:1) to placebo, PGB-CR 165 mg, or PGB-CR 330 mg for 14 weeks, including a 2-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…The 3 phase 3 studies were performed to evaluate the efficacy and safety of pregabalin ER in patients with postherpetic neuralgia, 15 fibromyalgia, 16 and partialonset seizures. 17 Exposures for pregabalin ER tablets administered QD after an evening meal in all 3 trials were similar to those for comparative doses of prega-balin IR capsules. Both the primary efficacy end point (ie, time to loss of therapeutic response) and a key secondary end point (ie, mean change from baseline) in a double-blind, placebo-controlled, randomized withdrawal trial of pregabalin ER (165-660 mg) demonstrated the efficacy of pregabalin ER in patients with postherpetic neuralgia.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The 3 phase 3 studies were performed to evaluate the efficacy and safety of pregabalin ER in patients with postherpetic neuralgia, 15 fibromyalgia, 16 and partialonset seizures. 17 Exposures for pregabalin ER tablets administered QD after an evening meal in all 3 trials were similar to those for comparative doses of prega-balin IR capsules. Both the primary efficacy end point (ie, time to loss of therapeutic response) and a key secondary end point (ie, mean change from baseline) in a double-blind, placebo-controlled, randomized withdrawal trial of pregabalin ER (165-660 mg) demonstrated the efficacy of pregabalin ER in patients with postherpetic neuralgia.…”
Section: Discussionmentioning
confidence: 68%
“…In a trial of similar design evaluating pregabalin ER (330‐495 mg) in adults with fibromyalgia, the primary efficacy end point (ie, time to loss of therapeutic response) was met, but the trial did not demonstrate efficacy in a key secondary end point (ie, mean change from baseline) . Similarly, a double‐blind, randomized, placebo‐controlled trial of pregabalin ER (165‐330 mg) in adults with partial onset seizures did not demonstrate that pregabalin is effective in reducing seizure frequency below that of placebo . In all 3 trials, the safety profile of pregabalin ER was comparable to that reported previously for the IR formulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study evaluated the efficacy and tolerability of adjunctive PGB as a controlled-release formulation. The 50% responder rate (ie percentage of patients achieving 50% reduction in seizure frequency) was 45.9% for a daily dose of 330 mg. 98 Another randomised study tested PGB versus LEV in a head-to-head comparison in 409 patients. The drug PGB was non-inferior to LEV with a similar tolerability to LEV as adjunctive therapy.…”
Section: Pregabalinmentioning
confidence: 99%